Web-Based Student Attendance Design At SMP Negeri 2 Baleendah - Asih Sri (PT. Banjarese Pacific Indonesia, 2024)
Schools are also not only a means to seek knowledge, but also to shape characters or attitudes in students, for example in terms of attendance or absence. Attendance is an element of discipline that aims to improve discipline in an institution. Therefore, an online-based attendance system is needed, where the teacher validates students directly using the attendance website through a computer or laptop. The model used for website design is the waterfall method. The results of this study are by designing a student attendance website where the teacher validates students directly using the attendance website so as to facilitate the process of making attendance reports as well as teachers who have validated students can be seen or monitored by the principal or admin as an alternative to solving problems that exist in SMP Negeri 2 Baleendah.